Reconstructing the ecosystem context of a species: Honey-borne DNA reveals the roles of the honeybee - Wirta Helena Kristiina; Bahram Mohammad; Miller Kirsten; Roslin Tomas; Vesterinen Eero (Public Library of Science, 2025)
To assess a species' impact on its environment-and the environment's impact upon a species-we need to pinpoint its links to surrounding taxa. The honeybee (Apis mellifera) provides a promising model system for such an exercise. While pollination is an important ecosystem service, recent studies suggest that honeybees can also provide disservices. Developing a comprehensive understanding of the full suite of services and disservices that honeybees provide is a key priority for such a ubiquitous species. In this perspective paper, we propose that the DNA contents of honey can be used to establish the honeybee's functional niche, as reflected by ecosystem services and disservices. Drawing upon previously published genomic data, we analysed the DNA found within 43 honey samples from Northern Europe. Based on metagenomic analysis, we find that the taxonomic composition of DNA is dominated by a low pathogenicity bee virus with 40.2% of the reads, followed by bacteria (16.7%), plants (9.4%) and only 1.1% from fungi. In terms of ecological roles of taxa associated with the bees or taxa in their environment, bee gut microbes dominate the honey DNA, with plants as the second most abundant group. A range of pathogens associated with plants, bees and other animals occur frequently, but with lower relative read abundance, across the samples. The associations found here reflect a versatile the honeybee's role in the North-European ecosystem. Feeding on nectar and pollen, the honeybee interacts with plants-in particular with cultivated crops. In doing so, the honeybee appears to disperse common pathogens of plants, pollinators and other animals, but also microbes potentially protective of these pathogens. Thus, honey-borne DNA helps us define the honeybee's functional niche, offering directions to expound the benefits and drawbacks of the associations to the honeybee itself and its interacting organisms.